Blood for the undying throne - Kim, Sŏng-il (Science fiction writer) (The bleeding empire, 2025)
"Blood for the Undying Throne, the sequel to Blood of the Old Kings, from award-winning Korean author Sung-il Kim and translated by the world-renowned Anton Hur, is an epic fantasy adventure where the corpses of sorcerers power an empire and ordinary people rise up to tear it down. Nothing can stop the Empire's insatiable conquest. Not gods, not dragons, not armies. But heroes still rise. The Empire continues to enforce its so-called peace with massive war machines that destroy anything that opposes their might. Though the conquered are wholly at the mercy of the Empire, desperate odds such as these can be fertile soil for heroic resistance. Last seen rallying under Loran's banner, Emere is now a powerless politician in the Imperial Capital. But when an assassination attempt is made on his life, he discovers that he may just be at the center of sinister plots brewing in the highest levels of the Empire. Arienne has crossed the continent on a mission to learn more about the Star of Mersia, the infamous yet mysterious weapon that decimated the country of Mersia in a single day. But when she arrives at the supposedly lifeless land, Arienne is shocked to find much more than ruins. One hundred and seventy years ago, before the Empire laid waste to its plains and its people, Mersia suffers under the whims of the ruthless Grim King Eldred. When Yuma, the chief cattle herder, meets an emissary from the Empire, she dares to hope that this foreign nation might have the power to overthrow the Grim King and end his reign of terror. But Yuma will learn, only once it's too late, that aligning with the Empire will have consequences that reverberate through the ages. Sacrifices must be made in the fight against tyranny, but some sacrifices may be too great"-- Provided by publisher.